FRI0635 ULTRASOUND IN THE ASSESSMENT OF TENOSYNOVITIS IN JUVENILE IDIOPATHIC ARTHRITIS: SYSTEMATIC LITERATURE REVIEW. (June 2019) - COLLADO, PAZ; Magni-Manzoni, Silvia; Steiner, Martina; Ting, Tracy; Fernandez, Patricia Vega; Malattia, Clara; Rodriguez, Ana; Bruyn, George; Keen, Helen; Terslev, Lene; ,
Abstract : Background: Tendon involvement is common in patients with juvenile idiopathic arthritis (JIA). Differentiating tenosynovitis and underlying arthritis may be challenging on the basis of clinical examination (CE) alone. In daily clinical practice, ultrasound (US) imaging with Doppler information can be more versatile as it allows a dynamic assessment of joint inflammation and can be done quickly at the bedside. US can reliably evaluate the location of inflammation and provide direct visualization when local steroid injection is considered as treatment for children with JIA. Objectives: To present the published data concerning the US assessment of tenosynovitis and the US metric properties investigated in JIA. Methods: A systematic literature review (SLR) was conducted comprising PubMed, Embase and the Cochrane Library (before June 2018). Search terms: "arthritis, juvenile" AND, "tenosynovitis OR tendinopathy" AND "ultrasonography" OR "Doppler" AND "diagnosis OR therapy management". Selection criteria: Original articles published in English reporting US, tenosynovitis and tendinopathy in the paediatric population (up to18 years old) with JIA. Data were extracted from manuscripts meeting the selection criteria, with particular focus on the definition used, scoring system applied and the US metric properties investigated. The quality of the studies was assessed using the same methodology developed for the SLR on paediatric synovitis [1]. Results: After selection, 11 articles were analysed. The tibialis posterior tendon group and peroneal tendons were the most commonly evaluated. Most authors applied the OMERACT definition proposed to rheumatoid arthritis (RA) [2] for evaluating paediatric tenosynovitis. Binary scoring system on both grey scale and Doppler was applied in most of studies. Doppler function was commonly included, with only five specifying the Doppler parameters that were used. Construct validity was reported in roughly 50% of articles, including the CE as the main comparator. However, some of those articles have shown that clinical evaluation underestimates tendon involvement. US reliability and responsiveness for tenosynovitis in JIA was rarely included. Conclusion: Although US seems a promising image modality to assess tenosynovitis in JIA, this SLR emphasizes the definitions of US elementary lesions of RA are frequently used in children. Moreover, there is insufficient evidence of studies exploring the construct validity of the US-determined tenosynovitis in JIA. Further validation studies are needed for implementation in clinical practice and trials. References: [1] Collado P. Arthritis Care Res2012; 64:1011 [2] Wakefield R. J Rheumatol. 2005;32:2485 Disclosure of Interests: PAZ COLLADO: None declared, Silvia Magni-Manzoni Consultant for: Abbvie, Speakers bureau: Abbvie, MARTINA STEINER: None declared, Tracy Ting : None declared, Patricia Vega Fernandez: None declared, Clara Malattia: None declared, Ana Rodriguez: None declared, George Bruyn : None declared, Helen Keen: None declared, Lene Terslev Speakers bureau: Speakers fee from : Roche, Novartis, Pfizer, MSD, BMS, Celgene